2016
DOI: 10.1007/s00262-016-1921-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils from chronic lymphocytic leukemia patients exhibit an increased capacity to release extracellular traps (NETs)

Abstract: Chronic lymphocytic leukemia (CLL) is characterized by immune defects that contribute to a high rate of infections and autoimmune cytopenias. Neutrophils are the first line of innate immunity and respond to pathogens through multiple mechanisms, including the release of neutrophil extracellular traps (NETs). These web-like structures composed of DNA, histones, and granular proteins are also produced under sterile conditions and play important roles in thrombosis and autoimmune disorders. Here we show that neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
0
40
1
Order By: Relevance
“…showed that a higher percentage of CD16 high CD62L dim neutrophils in HNSCC correlates with better clinical outcome because of the antitumor activity exerted by these cells through the release of NETs. By contrast, we previously reported in CLL that NETs promote leukemic cells survival and activation, suggesting that an increase percentage of the CD16 high CD62L dim subset could be detrimental instead of beneficial to CLL patients. Neutrophils displaying a B‐helper phenotype have been previously described at the marginal zone of the spleen where IL‐10 released by activated endothelial cells enable neutrophils to produce BAFF, APRIL and NET‐like structures that promote B‐cell activation.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…showed that a higher percentage of CD16 high CD62L dim neutrophils in HNSCC correlates with better clinical outcome because of the antitumor activity exerted by these cells through the release of NETs. By contrast, we previously reported in CLL that NETs promote leukemic cells survival and activation, suggesting that an increase percentage of the CD16 high CD62L dim subset could be detrimental instead of beneficial to CLL patients. Neutrophils displaying a B‐helper phenotype have been previously described at the marginal zone of the spleen where IL‐10 released by activated endothelial cells enable neutrophils to produce BAFF, APRIL and NET‐like structures that promote B‐cell activation.…”
Section: Resultscontrasting
confidence: 71%
“…Millrud et al 19 showed that a higher percentage of CD16 high CD62L dim neutrophils in HNSCC correlates with better clinical outcome because of the antitumor activity exerted by these cells through the release of NETs. By contrast, we previously reported in CLL that NETs promote leukemic cells survival and activation, 18 suggesting that an increase percentage of the CD16 high CD62L dim subset could be viable neutrophils (mean AE SD, n = 5 or 7, respectively). Statistical analysis was performed by Friedman test and Dunn's posttest.…”
Section: Neutrophils From Cll Patients Can Impair T-cell Responsesmentioning
confidence: 58%
See 1 more Smart Citation
“…IL-8 is one of the first cytokines described to act on B-CLL cells. Its serum concentrations are augmented in B-CLL patients compared to healthy controls, and it has been demonstrated that IL-8 increases B-CLL cell survival [104][105][106][107][108]. IL-8 participates via an autocrine modality to the B-cell accrual typical of this type of leukemia.…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 99%
“…Interleukin-8 (IL-8/CXCL8) is one of the first molecules reported to play a key role in CLL biology 4 . Its serum levels are increased in most patients compared to age-matched healthy donors 5 , 6 and it is widely accepted that IL-8 prolongs CLL cell survival in an autocrine fashion 5 , 7 9 . However, there is no reported evidence of the expression of IL-8 receptors, CXCR1 and CXCR2, on circulating CLL cells.…”
Section: Introductionmentioning
confidence: 99%